2021
DOI: 10.3390/cancers13061292
|View full text |Cite
|
Sign up to set email alerts
|

Targeting BCL-2 in Cancer: Advances, Challenges, and Perspectives

Abstract: The major form of cell death in normal as well as malignant cells is apoptosis, which is a programmed process highly regulated by the BCL-2 family of proteins. This includes the antiapoptotic proteins (BCL-2, BCL-XL, MCL-1, BCLW, and BFL-1) and the proapoptotic proteins, which can be divided into two groups: the effectors (BAX, BAK, and BOK) and the BH3-only proteins (BIM, BAD, NOXA, PUMA, BID, BIK, HRK. Notably, the BCL-2 antiapoptotic proteins are often overexpressed in malignant cells. While this offers sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 107 publications
(152 reference statements)
0
69
0
Order By: Relevance
“…In addition, the dual-luciferase activity assay revealed that BIK was a downstream target gene of miR-338, and miR-338 could conversely modulate BIK expression. The major form of cell death is apoptosis, which is a programmed event regulated by the BCL-2 family of proteins which can be divided into two groups: the effectors and the BH3-only proteins, including BIK [ 44 ]. Previously, miR-1306-5p overexpression has been indicated to alleviate injury caused by cerebral ischemia/reperfusion in vitro by targeting BIK [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the dual-luciferase activity assay revealed that BIK was a downstream target gene of miR-338, and miR-338 could conversely modulate BIK expression. The major form of cell death is apoptosis, which is a programmed event regulated by the BCL-2 family of proteins which can be divided into two groups: the effectors and the BH3-only proteins, including BIK [ 44 ]. Previously, miR-1306-5p overexpression has been indicated to alleviate injury caused by cerebral ischemia/reperfusion in vitro by targeting BIK [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genes were selected after literature review and in silico analysis of the TCGA set. The bcl-2 (b cell lymphoma 2) protein encoded by BCL2 is a major apoptosis regulator and has mainly antiapoptotic effects in many different cancer entities [16]. BRCA1 and BRCA2 code for the correspondent breast cancer type 1/2 susceptibility proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Total proteins were isolated from tissues and cells in RIPA reagent (Sigma-Aldrich), and 20 μg aliquot of that were subjected to western blotting assay to evaluate expression of special proteins related to apoptosis (Bcl2-associated X protein [Bax] [ 22 ]), autophagy (LC3 [ 23 ]) and metastasis (matrix metalloproteinase 9 [MMP-9] [ 24 ]). The primary antibodies including anti-LC3 (4600-1-AP, 1:2,500; Proteintech, Wuhan, China), anti-NPTX2 (10,889-1-AP, 1:1,000; Proteintech), anti-MMP9 (ab228402; 1:5,000; Abcam, Shanghai, China), anti-Bax (ab216494; 1:500; Abcam), and anti-β-actin (20,536-1-AP, 1:5,000; Proteintech) were incubated overnight at 4°C, and secondary antibody anti-Rabbit IgG (SA00001-2, 1:10,000, Proteintech) was incubated for 2 h at 25°C.…”
Section: Methodsmentioning
confidence: 99%